2002
DOI: 10.1046/j.1524-4725.2002.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Anogenital Warts by Pulsed Dye Laser

Abstract: Pulsed dye laser has been found to be safe, effective, satisfactory, and less traumatic compared to other options for treatment of perianal warts in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…The clearance rate varied according to site, with 99% for genitalia [9], which is similar to our results for the FPDL treatment. Tuncel et al reported a complete healing of extensive perianal warts in a healthy 3-year-old boy after one FPDL treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…The clearance rate varied according to site, with 99% for genitalia [9], which is similar to our results for the FPDL treatment. Tuncel et al reported a complete healing of extensive perianal warts in a healthy 3-year-old boy after one FPDL treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…114 It produces less pain and scarring than with CO2 laser treatment and has been used for facial warts and perianal warts in children. 20,138,139 Pulse dye laser has been reported to result in complete remission in 48% to 95% of cases. 102,137,[140][141][142][143][144][145][146][147] One study found no statistically significant difference among cure rates between pulsed dye laser (66%) compared to conventional cryotherapy or cantharidin therapy (70%).…”
Section: Neodymium:yag (Nd:yag) Lasermentioning
confidence: 99%
“…30 In children, there has been 1 case report of using a pulsed-dye laser in a 3-year-old to clear treatmentresistant perianal warts; however, more studies are needed to determine the safety and efficacy of lasers in children. 31 …”
Section: Physical Destructionmentioning
confidence: 99%